PREVALENCE OF MTHFR GENE 677C>T POLYMORPHISM IN THE PATIENTS WITH PSORIASIS VULGARIS - Borislav Dimitrov; Dimitar Gospodinov; Veronika Gincheva; Regina Komsa-Penkova (Peytchinski Publishing, 2021)
The study aimed to investigate the relationship between carriage of 677C>T polymorphism in the gene of methylene tetrahydrofolate reductase (MTHFR) and plaque psoriasis in patients in Bulgaria. We examined the prevalence of MTHFR C677T genotype in patients with psoriasis, as well as the relationship of the polymorphism with disease severity. Our study covered63 patients with psoriasis and 98psoriasis-free control subjects from northern Bulgaria. MTHFR677C>T genotype was verified by the PCR-RFLP method. There was no significant difference between carriage of TT genotype among the patients and controls: 12.7% versus 10.8 %in controls, OR 1.203, (CI 95% 0465-3.175), p>0.05 respectively. There was a higher PASI score in patients, carriers of TT genotype of MTHFR polymorphism 677C>T than in non-carriers, 28.18versus 24.87 respectively, but not significant. Conclusion: Carriage of TT genotype of MTHFR polymorphism 677C>T was not associated with Psoriasis Vulgaris in the northern Bulgarian population when compared to healthy controls.